(untitled) (Scientia Agricola, 2011)
Cytogenetic analysis of the Amazon stingless bee Melipona seminigra merrillae, by conventional Giemsa staining and C-banding, revealed a different chromosome number for Melipona: 2n = 22 for females and diploid drones while the haploid drones present n = 11. There is no evidence of B chromosomes. This result contrasts with previous studies, in which the chromosome number of 19 Melipona species was determined as 2n = 18 for females and n = 9 for haploid males. Based on cytogenetic information available for other Melipona species, we propose that M. s. merrillae has a more derived diploid number. This indicates that chromosome number is not a conservative characteristic within the genus as previously thought. Cytogenetic data for stingless bees are scarce, especially in Amazon region. Additional studies will be very important in order to promote Melipona karyoevolution discussion and consequently a taxonomy review.